Comparative study on microstructures and properties of Mn-containing and Mn-free bainitic steels. Issue 4 (3rd March 2020) - Long, Xiaoyan; Zhang, Ruijie; Zhang, Fucheng; Zhang, Ming
ABSTRACT: The effects of Mn on the microstructure and impact-abrasion wear resistance of bainitic steel were studied. Results showed that the Mn-containing steel possessed finer microstructure and higher volume fraction of retained austenite, in comparison with the Mn-free steel. This was caused by lower transformation temperature and higher strength of undercooled austenite. The weight loss of Mn-free steel varying with the impact load was larger than that of Mn-containing steel. High strength, hardness and toughness of Mn-containing steel were conducive to improving wear resistance. More retained austenite in Mn-containing steel played an active role in work hardening and hindering crack propagation. However, the portion of retained austenite that induced martensitic transformation was the same with increasing impact-wear load.